Wild pedigrees inform mutation rates and historic abundance in baleen whales - Suárez-Menéndez, Marcos; Bérubé, Martine; Furni, Fabrício; Rivera-León, Vania E; Heide-Jørgensen, Mads-Peter; Larsen, Finn; Sears, Richard; Ramp, Christian; Eriksson, Britas Klemens; Etienne, Rampal S; Robbins, Jooke; Palsbøll, Per J (Science (American Association for the Advancement of Science), 2023)
Phylogeny-based estimates suggesting a low germline mutation rate (μ) in baleen whales have influenced research ranging from assessments of whaling impacts to evolutionary cancer biology. We estimated μ directly from pedigrees in four baleen whale species for both the mitochondrial control region and nuclear genome. The results suggest values higher than those obtained through phylogeny-based estimates and similar to pedigree-based values for primates and toothed whales. Applying our estimate of μ reduces previous genetic-based estimates of preexploitation whale abundance by 86% and suggests that μ cannot explain low cancer rates in gigantic mammals. Our study shows that it is feasible to estimate μ directly from pedigrees in natural populations, with wide-ranging implications for ecological and evolutionary research.Phylogeny-based estimates suggesting a low germline mutation rate (μ) in baleen whales have influenced research ranging from assessments of whaling impacts to evolutionary cancer biology. We estimated μ directly from pedigrees in four baleen whale species for both the mitochondrial control region and nuclear genome. The results suggest values higher than those obtained through phylogeny-based estimates and similar to pedigree-based values for primates and toothed whales. Applying our estimate of μ reduces previous genetic-based estimates of preexploitation whale abundance by 86% and suggests that μ cannot explain low cancer rates in gigantic mammals. Our study shows that it is feasible to estimate μ directly from pedigrees in natural populations, with wide-ranging implications for ecological and evolutionary research.